2000
DOI: 10.4049/jimmunol.164.6.2871
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Defect Underlies B Lymphocyte Dysfunction in a Patient Diagnosed with Non-X-Linked Hyper-IgM Syndrome

Abstract: To establish the underlying cause of hyper-IgM syndrome in one female patient, B cell function was examined in response to CD40- and IL-4-mediated pathways. When CD40-induced functional responses were measured in unfractionated B cells, CD80 up-regulation, de novo Cμ-Cγ recombination, and Iγ transcription were all found to be relatively unaffected. However, CD40- and IL-4-mediated CD23 up-regulation and VDJ-Cγ transcription were clearly diminished compared to control cells. IL-4-induced CD23 expression was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…(C) Further analysis of the CD23b-II probe was performed with control D11 and pt1-LCL tet nuclear extracts. The following antibodies were added in increasing amounts to the indicated lanes: p50 (lanes 3-6), p65 (lanes 7-10), p52 (lanes [11][12][13][14], purified rabbit IgG (lanes 15-16), and c-Rel (lanes [17][18][19][20]. (D) EMSA with a probe that spans the identified NF-B binding site in the CD23a promoter (nucleotides Ϫ109 to Ϫ76).…”
Section: Decreased C-rel Expression In Pt1-lcl Tet Cells Is Not a Funmentioning
confidence: 99%
See 4 more Smart Citations
“…(C) Further analysis of the CD23b-II probe was performed with control D11 and pt1-LCL tet nuclear extracts. The following antibodies were added in increasing amounts to the indicated lanes: p50 (lanes 3-6), p65 (lanes 7-10), p52 (lanes [11][12][13][14], purified rabbit IgG (lanes 15-16), and c-Rel (lanes [17][18][19][20]. (D) EMSA with a probe that spans the identified NF-B binding site in the CD23a promoter (nucleotides Ϫ109 to Ϫ76).…”
Section: Decreased C-rel Expression In Pt1-lcl Tet Cells Is Not a Funmentioning
confidence: 99%
“…on March 28, 2019. by guest www.bloodjournal.org From through CD40 and characterized by aberrant CD23 expression. 17 Further work revealed that pt1-LCLs initially expressed a CD23 lo / CD38 hi phenotype, yet over time, a predominant population of CD23 hi /CD38 lo cells with increased mitogenic activity emerged from the initial CD23 lo population. However, using pt1-LCL tet cells expressing LMP1 under the control of a tet-inducible promoter revealed that CD23 surface expression did not increase throughout culturing even though proliferation was driven efficiently by LMP1 signals (Lu et al 18 and K.T.L.…”
mentioning
confidence: 99%
See 3 more Smart Citations